(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article revisits childhood autism, its impact on the body and physiological functions, and the fight against this disease. It analyzes recent publications on childhood autism, pediatric interventions, and preventive methods, as well as highlights issues and recommendations for future research and practical application.